A New Multichannel Spectral Imaging Laser Scanning Confocal Microscope. (26th March 2013) - Zhang, Yunhai; Hu, Bian; Dai, Yakang; Yang, Haomin; Huang, Wei; Xue, Xiaojun; Li, Fazhi; Zhang, Xin; Jiang, Chenyu; Gao, Fei; Chang, Jian
Abstract : We have developed a new multichannel spectral imaging laser scanning confocal microscope for effective detection of multiple fluorescent labeling in the research of biological tissues. In this paper, the design and key technologies of the system are introduced. Representative results on confocal imaging, 3-dimensional sectioning imaging, and spectral imaging are demonstrated. The results indicated that the system is applicable to multiple fluorescent labeling in biological experiments.